Reading china: Predicting policy change with machine learning - Weifeng Zhong; Julian TszKin Chan (American Enterprise Institute (AEI), 2018)
The authors develop a quantitative indicator of the Chinese government's policy priorities over a long period of time, which they call the Policy Change Index (PCI) of China.
Keywords: A; 330; China; Communist Party; Media and Technology; artificial intelligence (ai); Policy Change Index (PCI)